ENVIRONMENTAL EVALUATION OF THE MIDDLE SÃO FRANCISCO RIVER BASIN BETWEEN TRÊS MARIAS AND PIRAPORA, BY USING CHEMICAL AND GEOPHYSICAL INVESTIGATION IN SEDIMENTAL PROFILES FROM SELECTED MARGINAL LAGOONS. - Horn, Adolf Heinrich; Trindade, Wallace; Aranha, Paulo Roberto Antunes; Magalhães, Antônio; Torres, Isabela Claret (Geochimica Brasiliensis, 2018)
The industrial, farming and housing occupation of the upper to middle San Francisco basin is getting stronger, resulting in an increase of the environmental impact. Marginal lagoons, which are important support for wildlife and water supply are invaded during the flooding of the river and filled with material. The aim of this study was to characterize the particle size distribution, chemical and mineral development shown in the profiles of these marginal lagoons and correlate with the environmental evolution and impacts. Granulometric and geophysical studies were carried out using combined sieves, GPR, total chemical analysis by FRX and sequential leaching analyses by ICP-OES. The granulometric and mineralogical results showed a predominance of silt, alternating with sandy layers, indicating the annual and seasonal energy evolution and depositional source. Investigations with GPR show horizontal sets formed by the change of energy deposition. Selected elements (Ni, Zn, Co, As, Pb, Cu) showed a continue enrichment with higher concentration on the surface. All elements concentrations are related to the clay/silt fraction, thus allowing the use of this fraction for the investigation of the impact assessment. Cromium is related to sandy layers indicating its correlation with the mineral content. The positive correlation between Ni, Zn and Pb indicate industrial influence (refinement of Zn, heavy industry) the correlation Cu, Ni, Co and As may derive from the use of agro products. The elements Pb, Zn and Cu presented at the top of the profiles concentrations above legislation limits.